IDENTIFIKASI DAMPAK POTENSIAL PEMBANGUNAN TERMINAL TRANSIT DI BAU-BAU, PROPINSI SULAWESI TENGGARA - -, Achmad Sjafrudin (Fakultas Teknik Geologi Universitas Padjadjaran, 2008)
Fuel needs that keeps on increasing in Makasar can not be fullfilled by the Makasar installation, therefore it is necessary to built Bau-Bau Transit Terminal in Southeast Sulawesi Province.The construction will raise effects towards environment. Hence the needs of EIA study is very crucial to minimize all the effects that will appear in the future to support sustainable development.